Legal Implications of the Passive Account (Dormant) Blocking Policy on the Principle of Banking Secrecy in Indonesia - Rohmad Pujiyanto (Publikasi Indonesia, 2025)
This study analyzes the legal implications of blocking dormant accounts by the Financial Transaction Reporting and Analysis Center (PPATK) on the principle of banking secrecy in Indonesia. Banking confidentiality as a fundamental principle has been regulated in Law Number 7 of 1992 as amended by Law Number 10 of 1998, which confirms that banks are obliged to keep customer data confidential. However, there are exceptions in terms of prevention and eradication of criminal acts, especially money laundering as regulated in Law Number 8 of 2010 concerning TPPU. In practice, the authority of PPATK to temporarily suspend transactions or block passive accounts based on Presidential Regulation Number 50 of 2011 raises legal problems. On the one hand, this policy is needed to maintain the integrity of the financial system from the potential misuse of inactive accounts as a means of money laundering. However, on the other hand, these actions have implications for the protection of customer rights, the principle of banking secrecy, and the implementation of due process of law. The research method used is normative juridical with legislative, conceptual, and case approaches. The results of the study show that the legal basis for PPATK's authority is available, but its implementation causes legal uncertainty because there is no balanced mechanism between the state's interests in eradicating financial crimes and the protection of customers' constitutional rights. Therefore, it is necessary to harmonize regulations and reformulate the supervisory mechanism so that the authority of PPATK remains proportional, accountable, and in accordance with the principles of substantive justice